Proceedings of the 15th International Conference on Mining Software Repositories 2018
DOI: 10.1145/3196398.3196403
|View full text |Cite
|
Sign up to set email alerts
|

A benchmark study on sentiment analysis for software engineering research

Abstract: A recent research trend has emerged to identify developers' emotions, by applying sentiment analysis to the content of communication traces left in collaborative development environments. Trying to overcome the limitations posed by using off-the-shelf sentiment analysis tools, researchers recently started to develop their own tools for the software engineering domain. In this paper, we report a benchmark study to assess the performance and reliability of three sentiment analysis tools specifically customized f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 38 publications
7
89
0
Order By: Relevance
“…For instance, the Dissensus smell arises when developers are not able to reach a consensus with respect to the patch to be applied: likely, in this case the conversations among developers will report contrasting opinions that can be identified using opinion mining techniques or contrasting sentiment detectable using sentiment analysis [141]. In this regard, it is worth remarking that recent findings on sentiment analysis [142], [143] revealed that existing tools are not always suitable for software engineering purposes, thus suggesting that the ability of detecting community smells may depend on the advances of other research fields. At the same time, Code Red-which is the smell arising when only 1-2 maintainers can refactor the source code-may be structurally identifiable looking at the developers' collaboration network and applying heuristics to discriminate how many developers over the history of a class applied refactoring operations on it.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the Dissensus smell arises when developers are not able to reach a consensus with respect to the patch to be applied: likely, in this case the conversations among developers will report contrasting opinions that can be identified using opinion mining techniques or contrasting sentiment detectable using sentiment analysis [141]. In this regard, it is worth remarking that recent findings on sentiment analysis [142], [143] revealed that existing tools are not always suitable for software engineering purposes, thus suggesting that the ability of detecting community smells may depend on the advances of other research fields. At the same time, Code Red-which is the smell arising when only 1-2 maintainers can refactor the source code-may be structurally identifiable looking at the developers' collaboration network and applying heuristics to discriminate how many developers over the history of a class applied refactoring operations on it.…”
Section: Resultsmentioning
confidence: 99%
“…Although we involve both high-level attributes and keywords, some other characteristics such as review title length and post date, which would be helpful for response generation, are not considered. Besides, the review sentiment predicted by SentiStrength [40] might not be reliable [61], and could influence the generated response. However, accurate sentiment prediction based on reviews is out of the scope of this paper, and the effectiveness of StentiStrength in detecting user sentiment about app features has been demonstrated in [39].…”
Section: Threats To Validitymentioning
confidence: 99%
“…us, one possible way of addressing and performing the sentiment analysis would be adopting the work of [80,81] for Q&A posts. Nevertheless, another challenging issue that needs to be addressed is investigating the suitability of adopting different sentiment analysis techniques as reported in [82][83][84][85] for our domain.…”
Section: Need For Sentiment Analysismentioning
confidence: 99%